The role of the interleukin family in liver fibrosis - Zhang, Zixin; Wang, Jiahui; Li, Hui; Niu, Qun; Tao, Yujing; Zhao, Xin; Zeng, Zijian; Dong, Haijian (Frontiers in Immunology, 2025)
Liver fibrosis represents a wound-healing response to chronic liver injury caused by viral infections, alcohol, and chemicals agents. It is a critical step in the progression from chronic liver disease to cirrhosis and hepatocellular carcinoma. No chemical or biological drugs have been approved for the treatment of liver fibrosis. Relevant studies have demonstrated that effective inhibition of hepatitis B virus (HBV) replication by nucleoside (acid) analogs or polyethylene glycol alpha-interferon can lead to recovery in some patients with hepatitis B liver fibrosis, However, some patients with liver fibrosis do not show improvement, even after achieving a complete serologic and virologic response. A similar situation occurs in patients with hepatitis C-related liver fibrosis. The liver, with its unique anatomical and immunological structure, is the largest immune organ and produces a large number of cytokines in response to external stimuli, which are crucial for the progression of liver fibrosis. cytokines can act either by directly affecting hepatic stellate cells (HSCs) or by indirectly regulating immune target cells. Among these, the interleukin family activates a complex cascade of responses, including cytokines, chemokines, adhesion molecules, and lipid mediators, playing a key role in the initiation and regulation of inflammation, as well as innate and adaptive immunity. In this paper, we systematically summarize recent literature to elucidate the pathogenesis of interleukin-mediated liver fibrosis and explore potential therapeutic targets for liver fibrosis treatment.